International position of Poland and its foreign policy in the period 2002–2005 (Economic and Political Thought, 2015)
The period 2002–2005 was a specific time for the Polish foreign policy.On the one hand, our future membership in the European Union was beingclarified and, on the other hand, the involvement of Poland in the conflictsin Iraq and Afghanistan was growing. The article is an attempt to analyse theinternational position of Poland in the period and its influence of our foreignpolicy. One of the aims is to verify the thesis that the period 2002–2005was the end of a consensus on Poland’s foreign policy reached by the mainpolitical powers in Poland. The article deals with the following issues: theend of accession negotiations, the first year of membership, the role ofPoland in transatlantic relations and the policy of the authorities towardsEast European states.